Pharmacognostic and phytopharmacology study of Anacyclus pyrethrum: An insight - Afreen Usmani,Mohd Khushtar,Muhammad Arif,Mohd. Aftab Siddiqui,Satya Prakash Sing,Md Mujahid (Journal of Applied Pharmaceutical Science, 2016)
Anacyclus pyrethrum an amazing medicinal plant is one of the most widely growing species of the family Asteraceae. The present review endow with significant information about its phytochemical investigations, pharmacological activities and medicinal properties as a folk medicine to treat several disease like anti-rheumatic, analgesic, antibacterial, antiviral, carminative, anti-catarrh, improve digestion, emmenagogue, febrifuge, nervine, vermifuge, and sialagogue. The plant has been reported several pharmacological actions such as antidiabetic, immunostimulating effect, inhibitory effects, antidepressant activity, anticonvulsant activity, memory-enhancing activity, aphrodisiacs, antimicrobial activity, antioxidant, local anesthetic effect, insecticidal effect, action on COX and LOX, interactions with testosterone, interaction with libido, and it interaction with testicles. Mainly the root portion has beneficial properties that can serve the mankind. The entire plant can be extensively studied for further future prospective.
Keywords: Anacyclus pyrethrum,antimicrobial activity,phytochemical,anti-rheumatic,anticonvulsant activity.